Coffee consumption and reduced risk of hepatocellular carcinoma: findings from the Singapore Chinese Health Study - Johnson, Shane (2011)
BACKGROUND: Coffee consumption has been associated with reduced markers of hepatic cell damage, reduced risk of chronic liver disease, and cirrhosis across a variety of populations. Data on the association between coffee consumption and risk of hepatocellular carcinoma (HCC), especially in high-risk populations, are sparse. METHODS: This study examines the relationship between coffee and caffeine consumption, and the risk of developing HCC within the Singapore Chinese Health Study, a prospective cohort of 63,257 middle-aged and older Chinese men and women, a relatively high-risk population for HCC. Baseline data on coffee consumption and other dietary and lifestyle factors were collected through inperson interviews at enrollment between 1993 and 1998. RESULTS: As of 31 December 2006, 362 cohort participants had developed HCC. High levels of coffee or caffeine consumption were associated with reduced risk of HCC (p for trend < 0.05). Compared with non-drinkers of coffee, individuals who consumed three or more cups of coffee per day experienced a statistically significant 44% reduction in risk of HCC (hazard ratio 0.56, 95% confidence interval, 0.31–1.00, p = .049) after adjustment for potential confounders and tea consumption. CONCLUSION: These data suggest that coffee consumption may reduce the risk of developing HCC in Chinese in Singapore.